(3YedjGJ hLQGFe ZSjd GdCehGd EdcJQhfjG hCKQgG Ydi GdCReI GdEbJUGOjI GdYGdejI heSDhdjI GdHfhc hGdeUGQas - (3eMeO YHO GdSdGe(B, (3SdGeIs ((3GdbGgQI(B:s (3OGQ GdeYGQa(B,s, 2013)
(3jVe GdbhGYO GdehVhYjI hGdCQcGf GdbGfhfjI dLQjeI ZSjd GdCehGd , ecGaMI LQjeI ZSjd GdCehGd hGdYbGH YdjgG aj GdJTQjYGJ GdeNJdaI heOi UYhHI edGMbJgGs
Keywords: (3GdCReGJ GdEbJUGOjIs; (3GdHfhcs; (3LQGFe GdCehGds